A Comprehensive Study on Sustainable Photocatalytic Pervious Concrete for Storm Water Pollution Mitigation: A Review. (2017) - Hasan, M.R.; Zain, M.F.M.; Hamid, R.; Kaish, A.B.M.A.; Nahar, S.
Abstract: Pervious concrete is an exclusive type of concrete that permits high volume of water to pass through it and a photocatalyst is a material that has capacities as an impetus (changes the rate of a synthetic response) when presented with light. This paper reviews the scientific literature on the utilization of photocatalyst in pervious concrete for storm water purification. Environmentally friendly photocatalytic pervious concrete is used as a pollutant reducer for storm water. This paper discusses about principal tendencies of photocatalysts (like TiO2, ZnO, etc.) and their incorporation to the pollutant degradation process. It presents a summary of the photo induced redox response and tremendous-hydrophilic conversion of the degradation of pollutants in storm water. The study focuses the progress of photocatalytic pervious concretes, i.e., the synergy among photocatalytic materials in pervious concrete for storm water pollution treatment.